Efficient metasurface for electromagnetic energy harvesting with high capture efficiency and a wide range of incident angles - Ahmed Ghaleb Amer, Abdulrahman; Sapuan, Syarfa Zahirah; Ashyap, Adel Y. (Tayler & Francis, 2022)
This work introduces a miniaturized metasurface (MS) energy harvester operating at 5.54 GHz with a high capture efficiency and a wide incident angle. The proposed MS structure is comprised of an ensemble of electric ring resonator (ERR) array. The MS’s impedance is engineered to match free space, so that the incident electromagnetic (EM) power is efficiently captured with minimal reflection and delivered to the optimal resistor load through an optimally positioned metallic-via. According to the simulation results obtained by CST Microwave Studio, the proposed MS harvester achieves higher conversion efficiency of about 91% under normal incidence and more than 78% across a wider incident angle up to 60°. In order to verify the simulation results, a 5×5 cell array of the proposed MS harvester is fabricated and tested. The simulation and experimental results are well match. The proposed MS configuration can be attractive for high-efficiency and compact wireless sensor network harvesting systems.